Adoption of foreign institutional practices and industrial development: Understanding the cross-level interaction effects - Matenge, Tendy Moffat (Graduate School of Business (GSB), 2022)
Foreign market knowledge has been at the epicentre of international business research for decades and differences in institutional practices across countries have been found to influence performance of internationalised firms. Dominant scholarship in this area has been significantly influenced by insights and experiences from developed countries, usually to the detriment of understanding the influence of foreign institutional knowledge acquisition at both the firm and country levels in developing economies. Using a developing country lens, the objective of this study is to determine if foreign institutional practices acquired by SSA firms has a significant effect on their home country's industrial development. The study employs a quantitative cross-sectional survey research approach and collects data from 874 formally registered manufacturing firms in 28 SSA countries. The countries are stratified along two dimensions, noticeable and unnoticeable levels of industrial development. This allowed for cross-country comparison across the industrial development spectrum. The data collected was subsequently analysed in MLWin 3.02 for multilevel and involved a two-tier regression analysis to examine the relative importance of foreign institutional practice adoption as a source of variation in the home country's industrial development. The study finds statistically significant influences with respect to foreign practice adoption. This implies that adoption of foreign institutional practices by an internationalised firm from a foreign country benefits the home country. This study further opens new discussions about firm internationalisation and home country industrial development by demonstrating the significant influence of interaction effects between adoption of foreign institutional practices by an internationalised firm and four firm level variables and one country level variable on home country's industrial development.